The Influence of Pregnancy Exercises on the Smoothness of the First Stage of Labor in Mothers - Nikmah, Khusnul (Universitas Islam Lamongan, 2024)
Pregnancy exercise is part of antenatal care that pregnant women can do to face childbirth. The aim of this research was to see the effect of pregnancy exercise on the smoothness of the first stage of labor for women giving birth at TPMB Miftahul Khoiriyah, S. Keb. Bd Surabaya. This type of research is Quasexperimental with a static group comparison (Post Test) research design. The population in this study were all pregnant women. How to take samples Random sampling consisted of 10 people, 5 people did pregnancy exercise and 5 people did not do pregnancy exercise, then the length of the first stage of labor in each group was evaluated using a partograph sheet. Univariate and bivariate data analysis using the Chi-square test. Statistical test results show the influence of pregnancy exercise on the smoothness of the first stage of labor at TPMB Miftahul Khoiriyah, S. Keb. Bd Surabaya in 2023 with a p value of 0.002 at stage I. It was recommended to TPMB leaders Miftahul Khoiriyah, S. Keb. Bd Surabaya can maintain the pregnancy exercises that have been carried out and make this program into an SOP to smooth and speed up the birthing process.